Development Of Natural Fiber Reinforced Composite Prepreg - Ahmad Zahiri, Saifulmajdy (Universiti Sains Malaysia, 2018)
Generally, composite is a material made by mixing two or more constituent materials of different properties to enhance the advantages of the materials. Composite materials are highly utilized in lately due to their ability of tailored specified properties, such as high strength-to-weight ratio, corrosion resistance, inflammable properties, wear resistance and etc. The need for renewable fiber-reinforced composites has never been as prevalent as it currently is. Natural fibers offer cost savings and reduction in density when compared to glass fibers. Even though the strength of natural fibers is not as great as glass, the specific properties are comparable. In this study, mechanical properties of biocomposite materials of wet hand layup and prepreg using palm oil fiber, are to be analyzed and evaluated thoroughly. However, most of them will focus on the possibility to produce natural fiber prepreg composite and its characteristics. Fabrication methods includes compression molding, fiber separation and resin curingprocess used to manufacture the control specimens and prepreg Then, the mechanical properties of the specimens are tested using tensile test. There are a few issues encountered in this study as making prepreg is a complex process. The issues were solved through further research and development of the specimen. After the specimen produced tensile test was carried out for analysis and evaluation process. The results of specimen fabrication show that natural fiber prepreg fabrication is possible although its mechanical properties are less than fiberglass. In conclusion, natural fiber prepreg is possible to be developed. However, further research is needed to produce consistent and better natural fiber composite in the future.